Investigating the relationship between bad smells and bugs in software systems - Nascimento, Rogeres; Sant’Anna, Cláudio (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2017)
Bad smell is a design choice that can degrade different aspects of the source code quality of a software, such as comprehensibility and changeability. Researchers believe that the occurrence of bad smells can lead to the introduction of bugs during maintenance activities. However, there are few studies concerning the impacts of bad smells. Thus, in order to provide more experimental evidence about the impacts of bad smells on software development and maintenance, we conducted an experimental study aiming at investigating the relationship between the occurrence of bad smells and the occurrence of bugs. In this study we evaluated five open-source systems from the Apache community. The results show that classes with bad smells are slightly more related to the occurrence of bugs than classes without bad smells.